2013
DOI: 10.1161/circulationaha.113.001477
|View full text |Cite
|
Sign up to set email alerts
|

Acute Rheumatic Fever and Rheumatic Heart Disease

Abstract: Background-Although acute rheumatic fever (ARF) and its sequel, rheumatic heart disease (RHD), continue to cause a large burden of morbidity and mortality in disadvantaged populations, most studies investigating the effectiveness of control programs date from the 1950s. A control program, including a disease register, in the Northern Territory of Australia where the Indigenous population has high rates of ARF and RHD allowed us to examine current disease incidence and progression. Methods and Results-ARF and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
71
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(81 citation statements)
references
References 21 publications
8
71
2
Order By: Relevance
“…Furthermore, much of the currently available prospective data are from small pockets of highly susceptible indigenous groups in New Zealand and Australia. [6][7][8] The incidence of acute rheumatic fever (ARF), and RHD-related morbidity and mortality are thought to be unusually high in these groups. 7 These data may not be generalizable to the majority of those with RHD in LMICs because of differences in access to medical care and other socioeconomic factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, much of the currently available prospective data are from small pockets of highly susceptible indigenous groups in New Zealand and Australia. [6][7][8] The incidence of acute rheumatic fever (ARF), and RHD-related morbidity and mortality are thought to be unusually high in these groups. 7 These data may not be generalizable to the majority of those with RHD in LMICs because of differences in access to medical care and other socioeconomic factors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is limited information on the determinants of disease progression and on clinical outcomes in contemporary patients with RHD living in LMICs. 7 The Global Rheumatic Heart Disease Registry (REMEDY) was designed to help fill this knowledge gap. 3 We have previously reported the baseline characteristics of the 3343 patients recruited from 14 LMICs in REMEDY.…”
Section: Introductionmentioning
confidence: 99%
“…In New Zealand, between the years 2000-2009, and among children whose age was between 5 and 14 years, the incidence of acute rheumatic fever was found in Maori, non-Maori/Pacific, Pacific and all children 40.2/100.000, 2.1/100.000, 81.2/100.000 and 17.2/100.000, respectively. In the same study acute rheumatic fever incidence between the years 2000-2009 compared with 1993-2009 years, in 1993-2009 years acute rheumatic fever incidence was found in Maori and Pacific increased 79% and 73%, respectively, but in nonMaori/Pacific decreased 71% (25). Similarly, in New Zealand acute rheumatic fever incidence was found to be 3.1/100.000 and 46.1/100.000 in the region of Waikato and in the Maori population between the years 2002-2011, respectively.…”
Section: Discussionmentioning
confidence: 75%
“…Acute rheumatic fever incidence can be as high as 50/100.000. The highest incidence has been reported in Australia and New Zealand (19,25). Örün et al (12) reported the incidence of acute rheumatic fever as 21/100.000 in Central Anatolia region between 2000-2009 in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…There are upwards of 33 million patients with RHD, 275 000 deaths per year, and over 9 million Disability‐Adjusted Life Years lost 1. The prevalence peaks between 25 and 40 years of age, with a female predominance 2, 3. Heart failure symptoms, infective endocarditis, sudden death, atrial fibrillation, and embolic stroke are frequent complications 4.…”
Section: Introductionmentioning
confidence: 99%